The Effect of Advertising, Sales Promotion, Personal Selling and Brand Image on the Purchase Decision of Honda PCX Motorcycle in Surabaya - Zulkarnain Aji Putra; I Gede Arimbawa (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose:. This study aims to analyze the effect of advertising, sales promotion, personal selling and brand image on purchasing decisions for Honda PCX motorcycles in the city of Surabaya. Design/methodology/approach: The following research was conducted to analyze whether or not there is a relationship between the independent and dependent variables. Therefore, the researcher uses quantitative methods using objective measurements and mathematical analysis. The data analysis technique in this study used Multiple Linear Regression. The population in this study is people who use Honda PCX motorcycles, as many as 255 people. Findings: The results of data analysis of the influence of independent variables, namely Advertising, Sales Promotion, Personal Selling, and Brand Image on the dependent variable Purchasing Decision obtained Fcount 9.875 > 2.40 with a significance level of 0.000 < 0.05, which indicates that Advertising, Sales Promotion, Personal Salling and Brand Image positive and significant effect on the Purchase Decision on. The dominant variable that affects the Purchase Decision is the Brand Image variable. Research limitations/implications: The area determined in this study is the city of Surabaya. It is hoped that future research can further expand the research area to reach the province or country. It means that the remaining percentage is 41.6%. Other variables influence purchase decisions. With these results, it is hoped that future research can use other variables such as price, service after sales, and others variable Paper type: Research paper